Student’s Perception of TED TALK Video to Improve Listening Skill - Lidiyatul Izzah; Muhamad Sofian Hadi; Mutia Salma Rosa (Universitas Cokroaminoto Palopo, 2020)
This present study aimed at describing the students’ perception towards their listening skill and the media that used by the researcher is using TED TALK Videos. The study applied qualitative study with descriptive approach and the instrument using a questionnaire. A total of 10 questions were distributed to the participants. The participants who already filled the questionnaire are 30 participants. The result from 30 respondents’ through questionnaire indicates the students give a positive perception toward Ted Talk videos to improve their listening skill based on the overall data presented in the previous parts, it could be seen that the listening skills material which was equipped with TED Talk videos as a media to improve listening skill got a positive perception and great appreciation.